2018
DOI: 10.1038/s41598-018-24932-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 199a-5p induces apoptosis by targeting JunB

Abstract: MicroRNAs participate in a variety of physiological and pathophysiological processes in various organs including the heart. Our previous work revealed that the level of miR-199a-5p was significantly higher in failing hearts than in control hearts. However, whether it is associated with the progression of heart failure (HF) and mediates cardiomyocyte apoptosis remained unclear. In the present study, we used various biochemical and molecular biological approaches to investigate the changes in miR-199a-5p levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…NFKBIA played protective roles in myocardial injury by relieving inflammation through the inhibition of the NF‐κB signalling pathway (Figure 2). In addition, the information retrieval of these 4 genes in MI revealed that the involvement of CXCL8, CD44 and JUNB in the functional mechanism of MI has been reported, while few reports have investigated the role of NFKBIA in MI. Additionally, as NFKBIA was crucially involved in the NF‐κB signalling pathway, further investigations on NFKBIA are needed to acquire further insight into the functional mechanism of the NF‐κB signalling pathway in MI.…”
Section: Resultsmentioning
confidence: 99%
“…NFKBIA played protective roles in myocardial injury by relieving inflammation through the inhibition of the NF‐κB signalling pathway (Figure 2). In addition, the information retrieval of these 4 genes in MI revealed that the involvement of CXCL8, CD44 and JUNB in the functional mechanism of MI has been reported, while few reports have investigated the role of NFKBIA in MI. Additionally, as NFKBIA was crucially involved in the NF‐κB signalling pathway, further investigations on NFKBIA are needed to acquire further insight into the functional mechanism of the NF‐κB signalling pathway in MI.…”
Section: Resultsmentioning
confidence: 99%
“…We found that JUN proto-oncogene (JUN) is a key TF-modulating interconnector for other TFs ( Figure 15D). Levels of JunB are reduced in association with apoptosis in cultured cells [111].…”
Section: Transcriptional Regulation Is Impaired By Ptnpsmentioning
confidence: 96%
“…Figure 1B shows that crystalline PtNPs had the features of a Pt face-centered cubic (fcc) phase. First (111), second (200), and third (220) peaks corresponded to 2θ values of 41.9 • , 46.5 • , and 67.5 • , respectively. The X-ray diffraction (XRD) peaks of PtNPs were broad and comparable to those of the corresponding bulk Pt material.…”
Section: Synthesis and Characterization Of Ptnps Using Lycopenementioning
confidence: 98%
“…As the key regulator in the Wnt signaling pathway, miR-199a-5p induced muscle proliferation by targeting HIF-1, which is the key regulator in smooth muscle hypertrophy [36]. It also regulates cardiomyocyte apoptosis by targeting JunB (JunB proto-oncogene) [37]. In diabetic individuals, miR-199a-5p may be involved in skeletal muscle insulin resistance by inhibiting glucose transporter 4 (GLUT4) and hexokinase 2 (HK2) [38].…”
Section: Discussionmentioning
confidence: 99%